(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2016)
Introduction: Malnutrition is referred to as the greatest single threat to the world’s public health, especially for the developing countries. Childhood malnutrition is linked to slower cognitive development and serious health impairments later in life that reduce the quality of life of individuals. Nutritional status is determined anthropometrically and is a significant determinant of various types of morbidity and is associated with an increased risk of death from acute respiratory infection, diarrhoea, measles and few other infectious diseases. Objective: To assess nutritional status and disease profile of under five children in a rural area of Bangladesh. Materials and Methods: This cross-sectional study was conducted among 205 children with age between 1 to 59 months who were selected purposively. Two hundred five data were collected by interviewing the mothers of the children and also by reviewing the documents using a pretested semi-structured questionnaire and checklist. Nutritional status was assessed using WHO recommended Z-score category and Mid Upper Arm Circumference measurement. Results: Out of 205 children, more than half (57.6%) were girls and the rest of them were boys. About two-third of the children were aged between 25 and 59 months. Maximum (40.5%) mothers of the children had a background of secondary educational status and most of them (90.2%) were housewives. More than one-third (36.1%) of the respondents belong to families haveing monthly income between Tk. 5001 and 10,000 and the average income was Tk.14,544. About onethird (33.5%) of the children were stunted in Height for Age Z score. While 9.7% were moderately wasted and 1.5% were severely wasted in Weight for Height Z score. 3.8% of the children were severely underweight and 70.8% of the children’s weight was within the normal limit for their age. By Mid Upper Arm Circumference (MUAC) measurement, about 20.0% were of moderate acute malnutrition (MAM) and 1.1% were of severe acute malnutrition (SAM). Among the associated morbidities, diarrhoeal disease had highest prevalence (45%) followed by respiratory tract infection (38%) and pneumonia (18%). Conclusion: Under five children are the vulnerable segment of the population. The result demonstrates a high prevalence of malnutrition (especially stunting) among under five children in the study area. Considering the acute and long-term consequences of malnutrition, interventions aiming at reducing child malnutrition in such a population should focus on all the children of less than 5 years of age. Journal of Armed Forces Medical College Bangladesh Vol.12(1) 2016: 94-99